RETRACTED: Coniferous flour production peculiarities in the climatic conditions of the Far North - Zyryanov M.A.; Medvedev S.O.; Shvecova I.G. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001